Compact Circularly Polarized Antenna with a Capacitive Feed for GPS/GLONASS Applications - Jeong, Seong Jae; Hwang, Keum Cheol; Hwang, Do‐In (ETRI journal, 2012)
This letter presents a novel compact circularly polarized patch antenna for Global Positioning System/Global Navigation Satellite System (GPS/GLONASS) applications. The proposed antenna is composed of a simple square radiating patch fed by a capacitive dual‐feeder to increase the impedance bandwidth and a lumped element hybrid coupler to achieve the broadband characteristic of the axial ratio (AR). The realized antenna dimensions are 28 mm × 28 mm × 4 mm, which is the most compact size among the dual‐band GPS/GLONASS antennas reported to date. The measured results demonstrate that the proposed antenna has a gain of 2.5 dBi to 4.2 dBi and an AR of 0.41 dB to 1.51 dB over the GPS/GLONASS L1 band (1.575 GHz to 1.61 GHz).